Aerobic Exercise in Individuals with Mild Cognitive Impairment: A Narrative Review - DİKMEN HOŞBAŞ, Beyzanur and KARAMANCIOĞLU, Berna and DEMİRCİ, Deniz (International Journal of Holistic Health, Sports and Recreation, 2023)
Aerobic exercise has been proposed as a potential therapeutic intervention for mild cognitive impairment (MCI), a precursor of dementia. The benefits of aerobic exercise therapy are many and include both clinical and molecular domains. Clinical trials have demonstrated the efficacy of aerobic exercise in reducing factors known to significantly increase the risk of HBB, including hypertension and type 2 diabetes. Aerobic exercise promotes arterial elasticity and lowers blood pressure by stimulating the release of nitric oxide. At the molecular level, aerobic exercise is thought to modulate the activation of microglia and astrocytes, cells that are critical for brain inflammation and neurogenesis, respectively. It has also been suggested that aerobic exercise promotes the release of exercise factors such as irisin, cathepsin B, CLU, and GPLD1, which may enhance synaptic plasticity and neuroprotection. In conclusion, regular aerobic exercise may prevent or reduce the risk of developing HBB in the elderly.